Pengaruh Brand Awareness Dan Service Quality Terhadap Keputusan Pembelian Pada Konsumen Mixue Munjul Majalengka - Latief Z nur; Endah Prihartini; Septian Dwi Cahya Sudarman (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The large number of food and beverage businesses in Indonesia indicates thatthe level of purchasing decisions in Indonesia is high. The high enthusiasm of thecommunity makes companies have to compete to attract the attention of consumers so thatconsumers make purchases. One of the things a company can do to attract the attentionof consumers is Brand Awareness. If consumer awareness of the brand is low, then it iscertain that the brand equity will also be low. The other factor that also influences thepurchasing decision is Service Quality. Good Service Quality will affect profit andcorrelate with the results that will be obtained by a company. This study aims to determinethe effect of Brand Awareness and Service Quality on purchasing decisions for consumersof Mixue, Munjul Majalengka Branch.The method used in this research is descriptive and verification method. Thepopulation used is the consumer Mixue Branch Munjul Majalengka with a sample of 100people with a sampling technique using non-probability sampling with accidentalsampling. Data collection technique is by questionnaire. The analytical tools used in thisstudy are the classical assumption test, multiple linear regression, coefficient ofdetermination (R2), Model Feasibility (f test) and Hypothesis Test (t test).Based on the results of this study, it shows Brand Awareness has a positive andsignificant effect on purchasing decisions and Service Quality has a positive andsignificant effect on purchasing decisions.